Hedgehog Signalling Contributes to Trauma-Induced Tendon Heterotopic Ossification and Regulates Osteogenesis through Antioxidant Pathway in Tendon-Derived Stem Cells - Guanzhi Li; Ye Deng; Kaiqun Li; Yuchen Liu; Ling Wang; Zhiyong Wu; Chao Chen; Kairui Zhang; Bin Yu (MDPI AG, 2022)
Heterotopic ossification (HO) is defined as the generation of pathological ectopic bony structures in soft tissues, but the molecular mechanisms of tendon HO are not fully revealed. Hedgehog (Hh) signalling is reportedly critical in hereditary HO. Our study focuses on the role of Hh signalling in the formation of trauma-induced tendon ossification. In this study, samples of healthy tendons and injured tendons from C57BL/6J female mice at 1, 4, 7, and 10 weeks after Achilles tenotomy were collected for quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemical analysis (IHC). At 1, 4, 7, and 10 weeks postinjury, tendon samples from the mice administered with vehicle, GANT58 (a GLI antagonist), or SAG (a smoothened agonist) were harvested for micro-CT, histological staining, qRT-PCR, and IHC. Rat tendon-derived stem cells (TDSCs) treated with vehicle, GANT58, or SAG were used to induce osteogenic and chondrogenic differentiation in vitro for qRT-PCR, alkaline phosphatase staining, Alcian blue staining, and reactive oxygen species (ROS) levels measurement. We found that Hh signalling is remarkably activated during the formation of trauma-induced tendon ossification in the model of Achilles tenotomy. The in vitro and in vivo assays both confirm that downregulation of Hh signalling significantly suppresses osteogenesis and chondrogenesis to inhibit tendon ossification, while upregulation of Hh signalling promotes this process. Under osteogenic induction, Hh signalling regulates antioxidant pathway and affects ROS generation of TDSCs. Collectively, Hh signalling contributes to trauma-induced tendon ossification and affects ROS generation through antioxidant pathway in osteogenic differentiation of TDSCs, indicating that targeting Hh signalling by GANT58 may be a potential treatment for trauma-induced tendon ossification.